Plasma Clusterin Concentrations May Predict Resistance to Intravenous Immunoglobulin in Patients with Kawasaki Disease - Mei-Chen Ou-Yang; Ho-Chang Kuo; I-Chun Lin; Jiunn-Ming Sheen; Fu-Chen Huang; Chih-Cheng Chen; Ying-Hsien Huang; Ying-Jui Lin; Hong-Ren Yu (The Scientific World Journal)
Kawasaki disease (KD) is an acute febrile vasculitic syndrome of early childhood often complicated by coronary artery lesion that drastically reduces the quality of life. The study aimed to identify a reliable marker for predicting nonresponsiveness to the first course of intravenous immunoglobulin (IVIG) in KD patients. A total of 63 patients with KD were enrolled in the study (IVIG response, 58; IVIG resistance, 5). Plasma samples were collected before and after IVIG infusion for measurement of biomarkers. Patients’ clinical characteristics and laboratory data were also analyzed. A receiver operating characteristic curve was generated to identify a cut-off value for predicting IVIG resistance. Among the biomarkers, the difference in plasma clusterin concentrations before and after IVIG infusion (CLUSTER 12) was significantly related to IVIG resistance (P=0.040; 95% confidence interval (CI): −25.8% to −6.0%). Using a CLUSTER 12 cut-off value of <8.52 mg/L, the odds ratio for IVIG resistance was 11.467 (95% CI: 1.186 to 110.853). Patients with plasma CLUSTER 12 concentrations >8.52 mg/L had a much higher risk of IVIG resistance than those with CLUSTER 12 concentrations <8.52 mg/L. Plasma clusterin concentration shows promise as a candidate biomarker for predicting IVIG resistance in patients with KD.